2018
DOI: 10.1111/spol.12443
|View full text |Cite
|
Sign up to set email alerts
|

Practices of activation in frontline interactions: Coercion, persuasion, and the role of trust in activation policies in Germany

Abstract: Following Michael Lipsky's well‐known argument that policy is made in the daily encounters between street‐level bureaucracy and citizens, a growing body of research emphasizes that actors and organizations delivering social and labor‐market policy play a crucial role in welfare‐state politics. Using qualitative data collected at three local employment agencies in Germany, this article explores worker‐client relations as a crucial mechanism through which activation policies are translated into practice. The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 48 publications
5
31
0
4
Order By: Relevance
“…In line with earlier studies, we found that the observed activation strategies involved a mix of supportive and coercive elements (Sainsbury, 2008;Senghaas et al, 2018). The observed motivational strategies ranged from supportive (showing empathy and sharing experiences, to reminding clients of their legal duties) to specific cases that are more coercive (sanctioning).…”
Section: Conclusion and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with earlier studies, we found that the observed activation strategies involved a mix of supportive and coercive elements (Sainsbury, 2008;Senghaas et al, 2018). The observed motivational strategies ranged from supportive (showing empathy and sharing experiences, to reminding clients of their legal duties) to specific cases that are more coercive (sanctioning).…”
Section: Conclusion and Discussionsupporting
confidence: 88%
“…Welfare states try to encourage unemployed citizens to become economically self-sufficient through labour market activation policies (Considine, Nguyen, & O'Sullivan, 2018;Rice, 2013;Van Berkel & Borghi, 2007). Activation policies emphasize individual obligations in return for welfare benefits (Senghaas, Freier, & Kupka, 2018). Caseworkersin Dutch known as "klantmanagers"-play an important role in these policies, as they are responsible for making decisions about clients' activation trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the emphasis that those studies have placed on the interactive aspects of bureaucrats' performance, there are very few studies analysing how SLBs' personal networks influence policy implementation (Hupe & van Kooten, ). This is quite strange because policy implementation is an interactive process (Grindle, ; Hill, ; Lazin, ; Senghaas et al, ; Siciliano, ), with SLBs potentially playing the role of gatekeepers (Brodkin, ; Dubois, ) by connecting policy beneficiaries with socially constructed policies (Schneider & Ingram, ).…”
Section: Social Network and Relationships: Approaching Interactive Imentioning
confidence: 99%
“…The debates have underscored how various aspects associated with service users and organizational conditions or with bureaucrats' personal, social, and professional profiles affect their performance (Brodkin, ; Ellis, ; Ellis, Davis, & Rummery, ; Evans, ; Harrits & Møller, ; Hill, Hupe, & Buffat, ; Maynard‐Moody & Musheno, ; Møller, ; Møller & Stone, ; Tummers, ). The literature has also proven that policy implementation is an interactive process based on daily relationships between bureaucrats and their clients, peers, and superiors (Grindle, ; Hill, ; Lazin, ; Loyens, ; Marques, ; Matland, ; Senghaas, Freier, & Kupka, ; Siciliano, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hollertz, Jacobsson, and Seing's (2018) study concluded that performance targets divert street-level workers' attention away from clients' individual needs. At the same time, a German study pointed out that performance targets may motivate street-level workers to invest in relations with clients, in as far as they consider realizing these targets as a process of coproduction of workers and clients (Senghaas, Freier, & Kupka, 2018). Finally, tensions between street-level service personalization and standardization have also been discussed in the context of service provision models.…”
Section: Individual Action Plans and Personalizationmentioning
confidence: 99%